2004
DOI: 10.1080/00087114.2004.10589381
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the herbicide linuron on somatic chromosomes ofHelianthus annuusL. (Sunflower)

Abstract: -In this study the effects of the herbicide linuron on somatic chromosomes of Helianthus annuus L were investigated. The roots were treated with 30, 120, 240 and 500 ppm concentration of linuron for 3, 6 and 12 hours. The mitotic and phase indexes were determined and chromosomal abnormalities were investigated in both control and test groups. It was found that linuron had a marked mitodepressive action on mitosis. The types of chromosomal abnormalities observed included: fragments, disturbed metaphase, c-mitos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Linuron, a phenylurea-derived herbicide, is known as a mamalian carcinogenic agent (U.S. EPA 1995, Katsumata et al 2007. In Studies were shown that this herbicide causes several abnormalities in somatic chromosomes, single strain breaks in DNA and mitotic index decreases (Scassellati-Sforzolini et al 1997, Inceer et al 2004. These results of linuron also correlate with our results of linuron.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Linuron, a phenylurea-derived herbicide, is known as a mamalian carcinogenic agent (U.S. EPA 1995, Katsumata et al 2007. In Studies were shown that this herbicide causes several abnormalities in somatic chromosomes, single strain breaks in DNA and mitotic index decreases (Scassellati-Sforzolini et al 1997, Inceer et al 2004. These results of linuron also correlate with our results of linuron.…”
Section: Discussionsupporting
confidence: 84%
“…The frequency of the mitotic cell division in all groups treated with linuron was significantly reduced compared to the control group (Table 1). Similar results were observed in the meristematic stem of H. annuus cells treated with linuron (Inceer et al 2004).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The result is the formation of fragments that are similar to chromosome structures. This type of abnormality has been found in most studies with different chemicals [70,73,77,78,81].…”
Section: Discussionmentioning
confidence: 55%